Contrasting temporal dynamics of land surface temperature responses to different types of forest loss - Jing Li; Zhao-Liang Li; Xiangyang Liu; Yitao Li; Meng Liu; Nanshan You; Hua Wu; Lei He; Menglin Si; Ronglin Tang; Chenghu Zhou; Wei Zhao; et al. (The Innovation)
Forest loss impacts local climate through biophysical processes. However, our understanding of this impact remains limited due to the neglect of its temporal dynamics. Using a space-and-time scheme that incorporates a change-detection method, we assess the dynamics of land surface temperature (LST) responses to various forest-loss types. Globally, LST increased by 0.12 K one year after forest loss, followed by a decreasing trend of −0.14 K per decade. Deforestation driven by commodity production and urbanization results in persistent warming, while forest disturbances such as shifting agriculture, forestry, and fire trigger diverse response dynamics with significant spatial variation due to differences in subsequent vegetation recovery. These disturbances cause attenuated warming in low and mid-latitudes, while, in the boreal zone, contrasting dynamics are observed: shifting agriculture causes attenuated cooling, whereas forestry and fire result in enhanced cooling. In addition to amplifying the amplitude of the LST seasonal cycle, forest loss also shifts the seasonal phase, which has not been previously reported. These findings demonstrate that climate feedback from forest loss is climate specific, loss-type dependent, and time varying, providing new insights for the development of local climate policies.